2023
DOI: 10.1039/d2nr06042f
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive monitoring of biochemicals in hydrogel-assisted microfluidic chips

Abstract: A hydrogel acts as the sealing film of microfluidic chips, and allows the delivery of target biochemicals to the outer surface for various types of quantitative analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In our previous research, we found that hydrogel material can be ideal sealing film for microfluidics chip, in which water will not leak out but ions and small molecules can freely travel from the microchannel to the outer surface for detection. [ 24 ] Hence, it is possible that ion transport induced traditional streaming potential usually observed inside the channel can be detected outside the channel across a hydrogel sealing film. Measurement electrodes can thus be structurally simplified as a free moving probe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous research, we found that hydrogel material can be ideal sealing film for microfluidics chip, in which water will not leak out but ions and small molecules can freely travel from the microchannel to the outer surface for detection. [ 24 ] Hence, it is possible that ion transport induced traditional streaming potential usually observed inside the channel can be detected outside the channel across a hydrogel sealing film. Measurement electrodes can thus be structurally simplified as a free moving probe.…”
Section: Resultsmentioning
confidence: 99%
“…The pHEMA is chosen as a representative hydrogel to demonstrate the non‐invasive flow monitoring ability of our method considering both the monitoring performance and the fluid sealing ability reported in our previous work. [ 24 ] The details of the fabrication can be found in Experimental .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the fact that the hydrogel network reverted from the aggregated state to the original state in the cold environment, and the variation of individual fixed shapes was eliminated, resulting in a programmable effect. 46,47 Furthermore, the switching process of programmable hydrogels inspired us to develop temperature-sensitive security locks. As shown in Fig.…”
Section: Actuation and Shape Memory Behaviormentioning
confidence: 99%
“…8 But these methods require specific equipment and may not be suitable for handling viscous materials, often leading to cell damage. 8 Similarly, other hydrogel-based microfluidic preparation techniques, such as hydrogel-PDMS hybrid fabrication, [18][19][20] lightcontrolled degradation, 21 and direct writing, 22 also face challenges in constructing heterogeneous and accurate structures within hydrogels due to complications in handling, low resolution, or restriction to specific materials.…”
Section: Introductionmentioning
confidence: 99%